2014
DOI: 10.1210/en.2013-1447
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Glucagon-like Peptide-1 (GLP-1) Inhibits Eating in Male Rats by Acting in the Hindbrain and Without Inducing Avoidance

Abstract: To address the neural mediation of the eating-inhibitory effect of circulating glucagon-like peptide-1 (GLP-1), we investigated the effects of 1) intra-fourth ventricular infusion of the GLP-1 receptor antagonist exendin-9 or 2) area postrema lesion on the eating-inhibitory effect of intrameal hepatic portal vein (HPV) GLP-1 infusion in adult male rats. To evaluate the physiological relevance of the observed effect we examined 3) the influence of GLP-1 on flavor acceptance in a 2-bottle conditioned flavor avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 62 publications
4
59
0
Order By: Relevance
“…Systemic Ex4 activates GLP-1R receptors on the vagus nerve that in turn activate hindbrain NST relays; NST injections of Ex9 have been shown to impede satiation responses to gastric distension and hepatic portal glucose infusions (Hayes et al, 2009;Punjabi et al, 2014;Rüttimann et al, 2010). The PBN receives prominent and overlapping input from the rostral gustatory and caudal visceral sensory regions of the NST (Baird et al, 2001b;Fulwiler and Saper, 1984 and we have shown that gastric distension and gustatory stimuli modify electrophysiologically recorded neural impulse rates within the LPBN (Baird et al, 2001a, b), suggesting that PBN lesions would likely affect visceral and/or gustatoryrelated responses potentially affected by systemic Ex4.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic Ex4 activates GLP-1R receptors on the vagus nerve that in turn activate hindbrain NST relays; NST injections of Ex9 have been shown to impede satiation responses to gastric distension and hepatic portal glucose infusions (Hayes et al, 2009;Punjabi et al, 2014;Rüttimann et al, 2010). The PBN receives prominent and overlapping input from the rostral gustatory and caudal visceral sensory regions of the NST (Baird et al, 2001b;Fulwiler and Saper, 1984 and we have shown that gastric distension and gustatory stimuli modify electrophysiologically recorded neural impulse rates within the LPBN (Baird et al, 2001a, b), suggesting that PBN lesions would likely affect visceral and/or gustatoryrelated responses potentially affected by systemic Ex4.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, results vary substantially between studies and some suggest that GLP-1 in the circulation can reach any part of the brain, whereas others claim that GLP-1 is restricted to areas of the brain with a leaky BBB (44,72). The latter view was further substantiated by the finding that lesioning the area postrema blocked the effect of hepatoportal vein GLP-1 infusion (76). Additionally, in most rodent studies, peripherally administered GLP-1 retained its satiety effect after vagotomy or vagal deafferentation (33,108).…”
Section: Gut-derived Glp-1 and The Brainmentioning
confidence: 99%
“…Their findings suggest that the permeability of the BBB might be irrelevant for postprandial release of GLP-1 because rats that consumed a 3-g meal within 5-6 min, showed significant elevations in plasma GLP-1 only in the hepatoportal vein and not in the vena cava (76). This would suggest that under physiological conditions, GLP-1 receptors within the CNS are only reached by brain-derived GLP-1, suggesting a fundamental role for the PPG neurons.…”
Section: Gut-derived Glp-1 and The Brainmentioning
confidence: 99%
“…Likewise, when injected systemically, GLP-1 receptor agonists do not only affect the pancreas and gastrointestinal tract, but probably also the CNS. Thus, the nausea induced by peripheral administration of GLP-1 or exenatide (a GLP-1 agonist) seems to be caused by its direct action in certain brain regions (6,7); and some effects of the drug are mediated by the vagal afferents (8).…”
Section: Introductionmentioning
confidence: 99%